2015
DOI: 10.7326/aitc201507070
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease

Abstract: This issue provides a clinical overview of gastroesophageal reflux disease, focusing on diagnosis, treatment, and practice improvement. The content of In the Clinic is drawn from the clinical information and education resources of the American College of Physicians (ACP), including ACP Smart Medicine and MKSAP (Medical Knowledge and Self-Assessment Program). Annals of Internal Medicine editors develop In the Clinic from these primary sources in collaboration with the ACP's Medical Education and Publishing divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Laparoscopic antireflux surgery with fundoplication is a treatment alternative in patients with inadequate response to pharmacological treatment. 4,5 In contrast to medication, which reduces the acidity of the refluxate, antireflux surgery creates a mechanical barrier, preventing the refluxate from passing into the esophagus. Randomized clinical trials conducted in referral centers have shown a relatively low rate of reflux recurrence (up to 15%) after antireflux surgery.…”
mentioning
confidence: 99%
“…Laparoscopic antireflux surgery with fundoplication is a treatment alternative in patients with inadequate response to pharmacological treatment. 4,5 In contrast to medication, which reduces the acidity of the refluxate, antireflux surgery creates a mechanical barrier, preventing the refluxate from passing into the esophagus. Randomized clinical trials conducted in referral centers have shown a relatively low rate of reflux recurrence (up to 15%) after antireflux surgery.…”
mentioning
confidence: 99%
“…The corresponding GERD symptoms include heartburn, regurgitation, odynophagia, nausea, chest pain and coughing3. Without effective treatment, complications worsen and further develop into reflux esophagitis, esophageal strictures, and Barrett’s esophagus345, and in severe cases, esophageal adenocarcinoma may also occur67.…”
mentioning
confidence: 99%
“…The primary symptoms of GORD are heartburn and regurgitation of stomach contents. 2 Other, less common symptoms include chest pain, nausea, hoarseness and symptoms associated with bronchial aspiration of reflux contents reaching the oropharynx, for example, pneumonia, cough and other respiratory disorders. 2 The prevalence of GORD is estimated at 10%–20% in the USA and Europe, and less than 5% in Asia.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Other, less common symptoms include chest pain, nausea, hoarseness and symptoms associated with bronchial aspiration of reflux contents reaching the oropharynx, for example, pneumonia, cough and other respiratory disorders. 2 The prevalence of GORD is estimated at 10%–20% in the USA and Europe, and less than 5% in Asia. 3 The prevalence has increased during the last few decades, 4 an increase that correlates with the increasing prevalence of obesity, a known risk factor for developing GORD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation